Os jogos digitais como apoio pedagógico nas aulas de educação física escolar pautadas no currículo do Estado de São Paulo - Ferreira, Aline Fernanda [UNESP] (2014)
Physical Education with character renewing aims to provide learning on aspects related to the body and movement containing meanings in everyday life of the student. For this, education should be contextualized establishing, thus the student-teacher dialogue in the process of teaching and learning. The Information and Communication Technologies (ICT) dominate the daily lives of young people and their integration into the school environment aims to provide prospective citizens learning and resignification of knowledge present in your content. The digital games are an technologies that fastest growing sale and studies indicate tremendous educational potential when well articulated with the school content. In search of strategies to assist teachers in selecting and diversifying teaching methods and to bring the knowledge of body culture with the life of students, the aim of this study was to construct, implement and evaluate collaboratively with a teacher of Physical Education possibilities of using digital games as pedagogical support for teaching the content of the curriculum of the State of São Paulo for the 9th year of elementary school. Four lesson plans were developed with the inclusion of digital games to teach: Capoeira, Game and Sports, Baseball and Soccer. Besides a lesson to reflect on the influence of this technology in the lives of students. The classes were registered in the a diary and to complete the work and to know the impressions of the teacher and students participating in this study a semi-structured interview was conducted. The results of this study show the constructed lesson and analysis of the application of the same from the field diary and interviews. Data analysis were grouped into two broad categories related to the use of digital games in physical education classes: Contributions / possibilities and difficulties. As contributions/possibilities found that digital games helped the teaching of content in three...